POLISH TOURISM LAW AND THE EUROPEAN UNION LAW - Żegleń, Patrycja (Acta Scientiarum Polonorum. Oeconomia, 2010)
The article concerns the issues connected with tourism policy in the European Union, being a base for the other member countries, for example Poland. There are presented general and direct EU activities having an infl uence on tourism and having a refl ection in the law (directives, decisions, decrees) in that area. There is also an attempt to show law solutions connected with Polish law adjustment do the EU directives. Among the conclusions there is a statement that tourism policy is not always correct and sometimes in individual countries there is no need to unify the tourism law to the European level.